Vibration-Based Damage Detection With Structural Modal Characteristics - Yonggang Wang; Yulong Pei; Yangdon Zhao (The Baltic Journal of Road and Bridge Engineering)
A challenging problem in structural health monitoring systems is the requirement of a systematic, effective method for damage localisation and assessment severity of structures, based on vibration data measured by sensors. To address this issue, a novel technique, referred to as damage estimator with modal parameters of structure before and after damage, is applied to detect the location and estimate the severity of existing damage of complex structures. Specifically, a series of experimental tests using a scaled offshore platform model of a 4-story jacket type has been conducted to verify the efficiency of proposed approach, with white noise excitations applied to the top plate of test model. For 6 scenarios of damage conditions simulated by bolt adjustment in the 3rd layer, vibration-based impulse data are induced by an impact hammer and recorded to analyse the variations of modal parameters. Upon the investigation, the results highlight that damage estimator is capable of tracking damage orientation and severity longitudinally, using data from only the fundamental mode shape before and after damage. However, detection accuracy declines considerably for small-scale damages.